Deep Brain Stimulation in KMT2B-Related Dystonia: Case Report and Review of the Literature With Special Emphasis on Dysarthria and Speech - Abel, Maria; Pfister, Robert; Hussein, Iman; Alsalloum, Fahd; Onyinzo, Christina; Kappl, Simon; Zech, Michael; Demmel, Walter; Staudt, Martin; Kudernatsch, Manfred; Berweck, Steffen (Frontiers in Neurology, 2021)
Objective: KMT2B-related dystonia is a progressive childhood-onset movement disorder, evolving from lower-limb focal dystonia into generalized dystonia. With increasing age, children frequently show prominent laryngeal or facial dystonia manifesting in dysarthria. Bilateral deep brain stimulation of the globus pallidus internus (GPi-DBS) is reported to be an efficient therapeutic option. Especially improvement of dystonia and regaining of independent mobility is commonly described, but detailed information about the impact of GPi-DBS on dysarthria and speech is scarce. Methods: We report the 16-months outcome after bilateral GPi-DBS in an 8-year-old child with KMT2B-related dystonia caused by a de-novo c.3043C>T (p.Arg1015*) non-sense variant with special emphasis on dysarthria and speech. We compare the outcome of our patient with 59 patients identified through a PubMed literature search. Results: A remarkable improvement of voice, articulation, respiration and prosodic characteristics was seen 16 months after GPi-DBS. The patients' speech intelligibility improved. His speech became much more comprehensible not only for his parents, but also for others. Furthermore, his vocabulary and the possibility to express his feelings and wants expanded considerably. Conclusion: A positive outcome of GPi-DBS on speech and dysarthria is rarely described in the literature. This might be due to disease progression, non-effectiveness of DBS or due to inadvertent spreading of the electrical current to the corticobulbar tract causing stimulation induced dysarthria. This highlights the importance of optimal lead placement, the possibility of horizontal steering of the electrical field by applying directional stimulation with segmented leads as well as the use of the lowest possible effective stimulation intensity.